Quiescent Human Mesenchymal Stem Cells Are More Resistant to Heat Stress than Cycling Cells - L. L. Alekseenko; M. A. Shilina; O. G. Lyublinskaya; J. S. Kornienko; O. V. Anatskaya; A. E. Vinogradov; T. M. Grinchuk; I. I. Fridlyanskaya; N. N. Nikolsky (Hindawi Limited, 2018)
Quiescence is the prevailing state of many cell types under homeostatic conditions. Yet, surprisingly, little is known about how quiescent cells respond to environmental challenges. The aim of the present study is to compare stress responses of cycling and quiescent mesenchymal stem cells (MSC). Human endometrial mesenchymal cells (eMSС) were employed as adult stem cells. eMSC quiescence was modeled by serum starvation. Sublethal heat shock (HS) was used as a stress factor. Both quiescent and cycling cells were heated at 45°C for 30 min and then returned to standard culture conditions for their recovery. HS response was monitored by DNA damage response, stress-induced premature senescence (SIPS), cell proliferation activity, and oxidative metabolism. It has been found that quiescent cells repair DNA more rapidly, resume proliferation, and undergo SIPS less than proliferating cells. HS-enforced ROS production in heated cycling cells was accompanied with increased expression of genes regulating redox-active proteins. Quiescent cells exposed to HS did not intensify the ROS production, and genes involved in antioxidant defense were mostly silent. Altogether, the results have shown that quiescent cells are more resistant to heat stress than cycling cells. Next-generation sequencing (NGS) demonstrates that HS-survived cells retain differentiation capacity and do not exhibit signs of spontaneous transformation.